2016
DOI: 10.1186/s12929-016-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

The genetics and screening of familial hypercholesterolaemia

Abstract: Familial Hypercholesterolaemia is an autosomal, dominant genetic disorder that leads to elevated blood cholesterol and a dramatically increased risk of atherosclerosis. It is perceived as a rare condition. However it affects 1 in 250 of the population globally, making it an important public health concern. In communities with founder effects, higher disease prevalences are observed.We discuss the genetic basis of familial hypercholesterolaemia, examining the distribution of variants known to be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 89 publications
0
88
0
13
Order By: Relevance
“…PMI is a great life‐threatening disease, which is considered as one of the important clinical manifestations of FH. Therefore, screening for FH among PMI patients is significant . It has been shown that the prevalence of FH with common pathogenic gene mutations in PMI patients is about 1.3% to 7.0% .…”
Section: Discussionmentioning
confidence: 99%
“…PMI is a great life‐threatening disease, which is considered as one of the important clinical manifestations of FH. Therefore, screening for FH among PMI patients is significant . It has been shown that the prevalence of FH with common pathogenic gene mutations in PMI patients is about 1.3% to 7.0% .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, people with untreated FH are at a higher risk of coronary heart disease [57]. Genetic variants in three genes-low-density lipoprotein receptor (LDLR) [58], APOB, and proprotein convertase subtilisin/kexin type 9 (PCSK9) [59]-account for the majority of cases with autosomal dominant FH [60].…”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%
“…Although plenty of medications have been used by the aim of managing lipid profile and reducing the risk of cardiovascular diseases in FH patients, still it is not under control (37). Statins, which are the most efficient agents for alleviating LDL-C level, many of the patients treating with statins are incapable to tolerate them mainly because of muscle-related side effects or higher dose is required to attain the target LDL-C (38).…”
Section: Discussionmentioning
confidence: 99%